THE EFFECT OF PROMOTION COSTS AND GENERAL ADMINISTRATION COSTS ON NET PROFIT IN COSMETICS AND HOUSEHOLD NEEDS COMPANIES - MULYANA, ASEP; Habiburahman, Fadil (Department of Accounting, Faculty of Economics, Universitas Nurtanio Bandung, 2026)
Research This study aims to determine the effect of promotion costs and general administrative costs on net profit in cosmetics and household needs companies. to Net Income in cosmetics companies and household needs listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023, both the influence partially and simultaneously. The research method used in this research This research is a descriptive and associative method with a quantitative approach. This study uses secondary data, namely the financial statements of PT Victoria Care Indonesia Tbk, PT Martina Berto Tbk, PT Unilever Indonesia Tbk, and PT Kino Indonesia Tbk. Period 2020-2023. The data analysis technique used is multiple linear regression test, partial test (t test) and partial test (t test). partial test (t test) and simultaneous test (F test). The results showed that partially the variable Promotion Costs and General Administration Costs have no effect on Net Income. effect on Net Income. Simultaneously promotion costs and general administration costs Promotion costs and general administrative costs affect net profit in cosmetics companies and household needs listed on the Indonesia Stock Exchange (IDX) for the period of 2020-2023.